1996
DOI: 10.1116/1.588845
|View full text |Cite
|
Sign up to set email alerts
|

Stressing and high field transport studies on device-grade SiO2 by ballistic electron emission spectroscopy

Abstract: The tip of a scanning tunneling microscope was used to inject hot electrons across the gate and into the oxide of a metal-oxide-semiconductor structure. This method, known as ballistic electron emission microscopy ͑BEEM͒, allows an arbitrary choice of the energy of the injected electrons, which may be further accelerated by the application of a gate bias. The high current densities and choice of energy make BEEM an attractive method to study hot electron transport and breakdown phenomena in dielectrics. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…This high voltage low current imaging was done at the expense of lateral resolution, but was necessary to generate repeatable scans. Similar setpoint voltages with nanoamp currents have been used by others in STM experiments with thinner oxides, 25,29 as well as BASTM, 27 and BEEM 10,12,28 experiments. Initially the chips were scanned over 10 m to image the patterned circles to verify that our scan parameters were producing a reliable image.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This high voltage low current imaging was done at the expense of lateral resolution, but was necessary to generate repeatable scans. Similar setpoint voltages with nanoamp currents have been used by others in STM experiments with thinner oxides, 25,29 as well as BASTM, 27 and BEEM 10,12,28 experiments. Initially the chips were scanned over 10 m to image the patterned circles to verify that our scan parameters were producing a reliable image.…”
Section: Resultsmentioning
confidence: 99%
“…However ultrathin (Ͻ3.5 nm͒ layers of silicon dioxide, such as those used in the TSD, allow sufficient tunneling current to make STM a viable tool for examining local conductivity. Others have been able to study ultrathin oxides in experiments with beam assisted scanning tunneling microscopy ͑BASTM͒, 27 with BEEM, 10,12,28 and with STM of thinner oxides. 25,29 We have found that by operating at high tip voltages ͑1-5 V͒ and lower than usual tunneling currents ͑1-5 pA͒, the tip may be rastered over the silicon dioxide surface, yielding an image without crashing.…”
Section: A Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 As a main result, it was found that the breakdown of state-of-the-art gate oxides is still controlled by defects and impurities in the oxide and far away from the theoretical limit.…”
Section: ͓S0163-1829͑99͒06704-1͔mentioning
confidence: 98%
“…Such extreme low values are attributed to leakage of the trapped charge, a process believed to occur in the prebreakdown region. 28 The data presented in Fig. 3 correspond to the highest value measured at several stressing places for a given electron kinetic energy.…”
Section: A Observation Of Existing Traps and Mechanisms Of New Trap mentioning
confidence: 98%